The labour market impact of robotisation in Europe - José Ignacio Antón Pérez; David Klenert; Enrique Fernández-Macías; Maria Cesira Urzì Brancati; Georgios Alaveras (European Commission, Joint Research Centre (JRC), 2020)
This paper explores the impact of robot adoption on European regional labour markets between 1995 and 2015. Specifically, we look at the effect of the usage of industrial robots on jobs and employment structures across European regions. We regress the outcome of interest on the change in the exposure to robotisation in each regional labour market, based on the initial distribution of employment by industry across regions. Our estimates suggest that the effect of robots on employment tends to be mostly small and negative during the period 1995-2005 and positive during the period 2005-2015 for the overwhelming majority of model specifications and assumptions. Regarding the effects on employment structures, we find some evidence of a mildly polarising effect in the first period, but this finding depends to some extent on the model specifications. In sum, this paper shows that the impact of robots on European labour markets in the last couple of decades has been small and ambiguous. The strength and even the sign of this effect are sensitive to the specifications, as well as to the countries and periods analysed.
Keywords: 330; robots; employment; polarisation; robots and jobs; European Union